THE DYNAMIC OF NEGOTIATION PROCESSES BETWEEN GOVERMENT OF PHILIPPINES AND MORO ISLAMIC LIBERATION FRONT IN CONDUCTING PEACEFUL STETTLEMENT - Fajriyah Nurkhasanah taufik (Universitas Muhammadiyah Yogyakarta, 2011)
THE DYNAMIC OF NEGOTIATION PROCESSES BETWEEN GOVERMENT OF PHILIPPINES AND MORO ISLAMIC LIBERATION FRONT IN CONDUCTING PEACEFUL STETTLEMENT